Incidence of anemia in type 2 diabetic mellitus and its prognostic index - Periasamy, S.; Antony Xavier, Adhin; Gowtham, R. (International Journal of Medical Research and Review, 2016)
Objective: To identify the incidence of anemia in type 2 diabetic mellitus in a rural population and its prognostic value. Methodology: This is prospective observational study conducted at RMMCH, Chidambaram; the study comprises of 250 patients diagnosed with type 2 diabetic mellitus. Age of greater than 18 years, Risk factor such us hypertension and CAD were included in the study. Age of less than 18 years, anemia due to chronic blood loss, anemia due to other secondary causes and patient on treatment for anemia is excluded from the study. In patients with diabetic mellitus, HbA1c, Complete Blood Picture, Smear study, were done after obtaining consent detail from patients. Result: In the present study out of 250 populations females was dominated by 160/250(64%) with mean age group of 60±13 were mean duration of diabetes being 4.1±3 years and mean hemoglobin level was 11.3 ±2%, the comorbid condition such us CAD and Hypertension was present in 90 and 110 patients respectively. Mean HbA1c value was 8.4±2.1. Normocytic Normochromic anemia was present in 25% of anemic patients; Microcytic Hypochromic anemia was found in 35%, Macrocytic Hyperchromic is 32% and Dimorphic anemia was present in 8%. Conclusion: Anemia is present in 74% of the study population which point towards the need of hematological evaluations and care needed for the diabetic patients for better outcome in rural population.